Improvement of Dual Education in Professional Education - Rakhimova Farogatkhan Ikromovna (Researchparks Publishing, 2022)
In this article, the state of the professional education system of the Republic of Uzbekistan, the existing problems and shortcomings in the organization of dual education, their elimination and the issues of training competitive personnel, management of the quality of education, and development trends are reflected.